Creation of channeling electron-positron pair by a photon in the field of crystal planes; III International symposium Radiation from Relativistic electrons in periodic structures RREPS-97, September 8-12, 1997, Tomsk, Russia - Boev O. V. (1997, 1997)
В фонде НТБ ТПУ отсутствует